(untitled) (European Journal of Pure and Applied Mathematics, 2020)
Given a hyper BCK-algebra (H,*,0), we introduce some subsets of H and use them to generate two closure opeeatots on H. In this paper we show that each of tje two closurenoperators on H can be utilized to form a base for some topology on H.